Heparin use in acute coronary syndromes and cardiovascular interventions: habit or evidence based?. (20th January 2022) - Tan, Sean; White, Harvey D.; Layland, Jamie
Graphical Abstract: Graphical Abstract The evolution of heparin use in cardiology practice from 1916 to 2021. PTCA, percutaneous transluminal coronary angioplasty; PVI, pulmonary vein isolation; TAVR, transcatheter aortic valve replacement.